TRANSFORMASI NGEPAN TRADISIONAL PEREMPUAN IBAN PADA MASA KINI - AHMAD SHAFIQ, HUD (Universiti Malaysia Sarawak, (UNIMAS), 2016)
The research of the transformation of traditional Iban throughout nowadays. The traditional Iban women are among the flagship product of society itself, because of the uniqueness and beauty. This research aims to examine the characteristics and causes of transformation throughout the Iban traditional as well as measures to maintain the identity of the traditional clothing. The method the researchers use is the qualitative methods, better known as the interview. The original appearance of traditional women's clothing throughout Iban today has undergone many changes due to the passage of time and the influence of environment. Product changes from the traditional to the modern is going to drop even cause the fixings should be reduced or converted to another form because the material used is not the same as the old. Transformation throughout Iban profound impact on the identity and cultural heritage in the Iban community.